Comparison and Evaluation of Four Species of Macro-Algaes as Dietary Ingredients in Litopenaeus vannamei Under Normal Rearing and WSSV Challenge Conditions: Effect on Growth, Immune Response, and Intestinal Microbiota - Niu, Jin; Xie, Jia-Jun; Guo, Tian-Yu; Fang, Hao-Hang; Zhang, Yan-Mei; Liao, Shi-Yu; Xie, Shi-Wei; Liu, Yong-Jian; Tian, Li-Xia (Frontiers in Physiology, 2019)
The study was conducted to compare and evaluate effects of four different macro-algaes on growth, immune response and intestinal microbiota of Litopenaeus vannamei. In the rearing trial 1, shrimp were fed five diets containing four sources of macro-algaes for 8 weeks, named D1 (without macro-algae), D2 (Porphyra haitanensis), D3 (Undaria pinnatifida), D4 (Saccharina japonica) and D5 (Gracilaria lemaneiformis) respectively. Growth performance of shrimp in D5 diet was significantly higher than that of shrimp fed the control and D4 diet (P<0.05), however, there is no significant difference among D2, D3 and D5 diets (P>0.05). Apparent digestibility coefficiencts (ADCs) of dry matter from the D2, D3 and D5 diets were significantly higher than that from the control and D4 diets (P<0.05). Supplementary macro-algaes enhanced hepatopancreas immunity through positively increasing total antioxidant status (TAS) and prophenoloxidase activity (ProPO), as well as up-regulating the hepatopancreas RNA expression of ProPO and IκBα and down-regulating the expression of TGF-β. Furthermore, dietary macro-algaes modified intestinal microbiota of L. vannamei, boosting the relative abundance of beneficial bacterial such as Bacteroidetes, Firmicutes and Bacillaceae, and decreasing those detrimental bacterial such as Gammaproteobacteria and Vibrionaceae. In the WSSV challenge trial, shrimps were injected white spot syndrome virus (WSSV) for 6-day after the rearing trial. On the fourth day, shrimp death started to occur, and the mortality in D2, D3 and D5 diets were significantly lower than that in control and SJ diets during 4-6 challenged days (P<0.05). Dietary macro-algaes ameliorated hepatopancreas damage in L. vannamei by increasing TAS and ProPO activities and decreasing superoxide dismutase activity (SOD), inhibiting the lipid peroxidation (MDA), as well as regulating the immune-related genes expression. Taken together, dietary macro-algaes availably relieved enterohepatic oxidative damage by improving antioxidant ability and immunity and regulated intestinal microbiota in L. vannamei. These results indicated that G. lemaneiformis is the most suitable macro-algae and then followed by U. pinnatifida and P. haitanensis as the feed ingredient for L. vannamei.